2015
DOI: 10.1007/s00404-015-3796-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fetal cardiac anomalies on ductus venosus and aortic isthmus doppler profiles

Abstract: DV doppler studies in the second or third trimester may not be suitable as a screening test for congenital heart disease, but AI doppler studies might be considered as a supporting parameter. But further studies are needed for routine clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, after subgrouping by anomaly, the limited sample size restricted the significance of this finding. The largest subgroups included tetralogy of Fallot (13 fetuses) and muscular VSD (n = 10), for which statistically lower IFI values were seen [61]; the study concluded that AoI Doppler profiles might increase the sensitivity of CHD diagnosis.…”
Section: Aoi In Structural Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, after subgrouping by anomaly, the limited sample size restricted the significance of this finding. The largest subgroups included tetralogy of Fallot (13 fetuses) and muscular VSD (n = 10), for which statistically lower IFI values were seen [61]; the study concluded that AoI Doppler profiles might increase the sensitivity of CHD diagnosis.…”
Section: Aoi In Structural Pathologymentioning
confidence: 99%
“…Only one case-control study explored the IFI in CHD [61], finding a statistical difference in the overall sample of 64 fetuses with various types of CHD. However, after subgrouping by anomaly, the limited sample size restricted the significance of this finding.…”
Section: Aoi In Structural Pathologymentioning
confidence: 99%
“…In fact, competence in Doppler assessment of the DV is achieved only after extensive supervised training [34]. The evaluation of the DV flow can be made in the first [35][36][37][38][39][40] or second and third trimesters of pregnancy [41][42][43][44][45][46][47][48][49] (Figures 2 and 3). The DV can be visualized in a midsagittal longitudinal plane of the fetal trunk or in an oblique transverse plane through the upper abdomen [50].…”
Section: Fetal Ductus Venosus Flow Assessment In Daily Clinical Practicementioning
confidence: 99%
“…The left ventricle (LV) perfuses the coronary and brachiocephalic circulations, while the right ventricle (RV) the subdiaphragmatic circulation and placenta 3,4 . Retrograde flow (RF) may occur in the aortic isthmus (AI), the segment between the left subclavian artery and the ductus arteriosus (DA) insertion in the descending aorta 5–10 in fetuses with intra‐uterine growth restriction (IUGR), small for gestational age (SGA), 10–27 and some congenital heart disease (CHD), 28–30 such as transposition of great artery (TGA). However, RF in various fetal heart disease (FHD), including abnormalities in heart structure and function, and its association with flow variables has not been systematically studied 8,21 …”
Section: Introductionmentioning
confidence: 99%